Políticas de educação especial no município de Sorocaba, de 1988 a 2012 - Públio, Patrícia Lopes Ramos (Universidade Federal de São Carlos, 2016)
The presente stud has as object the research analysis of the contexts of production of special education public policies on municipal de Sorocaba/SP in 1988 to 2012 period, in seeking to understand the production and negotiations about their meanings in ensuring the right to education. The research is methodologically and theoretically reference in the policy cycle approach formulated by Stephen Ball and contributors that highlighting the complex and controversial nature of educational policy, proposing the existence of a political cycle: the context of influence, the context of text production, the context of practice. For the analysis of specific fields sought to complementarity in the grounds of authors about the conceptions of the role of the State, public policy (educational) and the right to education. This methodological approach, built on a qualitative analysis, taking as axis the documental analysis and literature analysis. The survey reveals that the process of special education in the city, constituted in this period of twenty-five years, in each period sought to adjust the settings of the policies under discussion at the time (national and international), demonstrating how the context of influence was decisive. This process has advanced regarding the actions undertaken by the secretary of education in their government projects, however, for not consolidating as municipal public policy, ensuring the permanence of the rights conquered becomes fragile leaving open the possibility of disruptions. So the research reveals that the practice context is beyond the municipality’s text production context.
Keywords: Educação especial - Política governamental - Brasil; Educação especial - Sorocaba (SP); Educação e Estado; Políticas públicas educacionais; Ciclo de políticas; Special education; Education and state; CIENCIAS HUMANAS::EDUCACAO